Hypersingular integral equations for arbitrarily located planar cracks in an anisotropic elastic bimaterial - Ang, W.T.; Park, Y.S. (Elsevier Ltd., 1997)
Hypersingular integral equations are derived for the problem of arbitrarily located planar cracks lying in the interior of two dissimilar anisotropic elastic half-spaces which adhere perfectly to each other. The unknown functions in the integral equations are the crack-opening displacements. The integral equations are solved numerically for specific examples involving particular transversely isotropic materials in order to compute physical quantities of interest such as the crack tip stress intensity factors or the crack energy.